KARAKTERISTIK PENDONOR DARAH ULANG DI UNIT DONOR DARAH PALANG MERAH INDONESIA PROVINSI SULAWESI UTARA - Posumah, Kezia Natasha; Berhimpong, Marnex; Pongoh, Lucyana (JURNAL ILMIAH KESEHATAN MANADO, 2024)
Abstract This research focuses on the characteristics of re-donor blood in the Indonesian Red Cross Blood Donor Unit in the North Sulawesi Province from 2019 to 2022. The main objective of this study is to understand the demographic characteristics and types of donors who participate in blood donor activities. The study used a descriptive method with a quantitative approach, collecting secondary data from PMI records. Data analysis showed that the majority of donors were males aged 25-44, and the most frequently donated blood type was blood type O. The findings are expected to help PMI develop more effective strategies to attract potential donors, especially within the identified demographic group.